CORRUPTION IN HEALTHCARE SYSTEM: AN OBSTACLE IN ACHIEVING OPTIMAL OUTCOME - Haroon, Muhammad Zeeshan (Journal of Ayub Medical College Abbottabad, 2014)
Corruption is one of the oldest and most prevalent social evil that has existed throughout the history of human kind and will remain a permanent reality. Corruption can be broadly defined as abusive use of power with the purpose of satisfying personal or group interests.1 The consequences of corruption not only hurts individual but also affects societies and national and international economies. When corruption is viewed at a macro level, it poses an obstacle to organization, government or state to deliver or fulfil its functions and obligations in resource allocation, policies and service delivery.2 The fact that corruption effects multiple dimensions of society, it cannot be defined by single universal definition rather can be defined addressing individual affected dimensions. As the market economy has gradually replaced our social system, the risk factors for corruption have increased greatly and it became a highly specialized phenomenon. Public companies, enjoying unchallenged position in market and wielding their power recklessly, forms the basis of corruption whereas union of economic and political interests provide favourable setting for corruption to thrive. Health being one of the most essential and basic needs of an individual makes it a lucrative target for corruption. Health having unique dimensions is susceptible to both economic and political influences and its corruption not only involves monetary incentives but also involves corruption of knowledge.3 This kind of corruption encompasses distorted facts and partial presentation of evaluation or evidence of research to mislead and to gain unfair edge or market position. Health sector is often ranked among the most corrupt systems in many developing countries. Perception survey on corruption conducted in 23 countries identified health sector to be ranked in the top four in ten countries.4 Modern health sector has a questionable history, driven by hunger of profit through the inhibition and discouragement of less profitable therapies and treatments. There are many areas in health care system which on given occasions allow dubious practices including corruption to pierce the barriers of health system. Incompetence and lack of administrative and public control, which is wrongly argued by the fact that the public lack expertise for involvement and control, serves as an entry point for corruption to seep in. Health care managers and professionals are usually resistant to accept public participation in decision making but on the other hand most of them show very little resistance in accepting benefits and offerings from the drug and equipment conglomerate. In many countries patients are forced to pay for accessing health care services (out of pocket payments) even when they are insured or entitled to free services. In addition to doctors accepting informal payments from patients they also moonlight.4 Moonlighting is unorthodox form of corruption as it is not usually identified with theft or use of public office for private gain.5 In developed countries where people enjoy health insurance, health care providers usually advise unnecessary medication, therapeutics and diagnostics procedures which have little or no added therapeutic benefits but have monetary percentages for the prescribers These professional misconducts can thrive in system where there are inadequate control or corrupt monitoring and evaluation mechanisms which is especially true for developing countries where the systems lack transparency and political or public oversight. Health sector corruption is not only rampant in developing countries, USAwhich is one of the most developed countries and having highest budget for health is also affected extensively. In 2010, 5.6 billion dollars were recovered in fraud and more than half, around 2.9 billion dollars were attributed to fraud in health care sectoralone.6 Pakistanbeing a developing country is also overwhelmed by corruption in its health care system. A study conducted in slums of Karachiindicated that 68.1% of the respondents perceived that corruption is higher in the government hospital as compare to the private hospitals. About 17.8% patients who seek care at hospital faced corruption in order to get admitted to these hospitals. Data also indicates the staffs dealing with admission, laboratory staff dealing with the provision of blood to the patients and pharmacy staff is the most corrupt. Seventy percent respondents claim that they have paid money as bribe to them followed by twenty four percent respondents claiming that they have paid money as bribe to the doctors. Those who paid bribes to get access to medical care, 52% did so by paying directly to the health care provider.7 Preventing and reducing corruption in health sector is a difficult task particularly development of effective auditing and accountability system to monitor and enforce appropriate laws. In order to curb the influence of corruption in health sector, health governance needs to be improved which involves a transparent policy and decision making processes involving all the stake holders and interest groups such as big Pharma to influence policy makers at level playing field with equal opportunities and can be ensured by fair rules of interest group competition.8 This level playing field for the interest group will also tend to reduce unfair lobbying which in turn will decrease opportunities for corruption and improve health care delivery responsiveness to the population especially the vulnerable groups. It is becoming increasingly clear that all stakeholders of health system including - politician, policy makers, health care providers, non-state actors and especially citizens need to be engaged. The myth of civil society not capable enough to sit on policy matters needs to be debunked and health care providers needs to accept their role in development of transparent and responsive health care system. Locally organized oversight by the civil society has shown a lot of promise based on experiences in Ceara, Braziland in Bolivia.9 At central level, Governments must disseminate easy to understand detailed budget and financial information related to health readily available to public which can then be easily tracked. Adequate pay and performance based financial incentives must be ensured by the government for the health care providers to improve their job satisfaction and in return will make them less vulnerable to corruption and bribery. Informal payments can be limited through setting up alternative sources of funding and better management. When official fee was raised as an alternate to informal payment, it improved patient payment and utilization in two pilot programs in Kyrgyz Republic, and in Cambodia where patients spending declined by 20 percent and 50 percent for drugs and supplies, respectively.9 Corruption is an intricate issue which not only threatens equity but also health outcomes. Progressively more and more health sector leaders are accepting the adverse effects of corruption and the need to address these issues has gain grounds in their policies. Efforts to segregate specific dimensions of corruption in the health sector and to understand its underlying cause can assist in curbing the issue. Applying different contextual theories to local settings can make more appropriate operational programs to reduce opportunities, increase pressure on care providers and decision makers and advocate more transparency to ensure the overall goals of health system.